2022
DOI: 10.1038/s41574-022-00746-8
|View full text |Cite
|
Sign up to set email alerts
|

The multiple roles of life stress in metabolic disorders

Abstract: The stress response is evolutionarily conserved across vertebrates to maintain homeostasis, but in excess can be damaging for body functions. We review the most recent research from basic sciences and epidemiology linking stress to the development and progression of metabolic disorders across the life course. Findings from rodents demonstrate that stress can affect features of metabolic dysfunction, such as insulin resistance, glucose and lipid homeostasis, as well as fundamental ageing processes such as cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 187 publications
1
36
0
4
Order By: Relevance
“…Across the 4 neuropsychiatric disorder groups, the metabolic, hepatic, and immune systems consistently showed poor health scores. Poor metabolic health is consistent with the commonly reported increased risk of developing metabolic diseases, including diabetes, metabolic syndrome, and obesity, in people with mental illness and may be partly attributable to adverse effects of antipsychotics and chronic stress . Chronic psychological stress is associated with mental illness and leads to dysregulation of the hypothalamic-pituitary-adrenal axis and endocrine and metabolic systems .…”
Section: Discussionsupporting
confidence: 88%
“…Across the 4 neuropsychiatric disorder groups, the metabolic, hepatic, and immune systems consistently showed poor health scores. Poor metabolic health is consistent with the commonly reported increased risk of developing metabolic diseases, including diabetes, metabolic syndrome, and obesity, in people with mental illness and may be partly attributable to adverse effects of antipsychotics and chronic stress . Chronic psychological stress is associated with mental illness and leads to dysregulation of the hypothalamic-pituitary-adrenal axis and endocrine and metabolic systems .…”
Section: Discussionsupporting
confidence: 88%
“…Increased social expenditure was associated with an increase in life expectancy, similar to what previous studies in multiple countries have reported ( Bergqvist et al, 2013 ; Bradley et al, 2011 ). This finding may underlie the protection of high social expenditure from the adverse health effects of poverty, by allowing people to invest in human capital such as education ( Reynolds & Avendano, 2018 ), and reducing exposure to health risk factors, such as chronic stress which has been linked to various cardio-metabolic disorders ( Kivimäki et al, 2022 ). Social expenditure is theorized to strengthen human agency and support peoples’ capacities to deal with stressful life events ( Dahl & van der Wel, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of loneliness and chronic social isolation in humans and animal models have consistently found an overactivation of the HPA axis, supported by findings of higher cortisol awakening responses (CAR), greater total GC output (area under the curve; AUC), and flattened diurnal cortisol rhythms in lonely individuals ( 33 39 ). Persistently high cortisol levels are associated with far-reaching physiological consequences, including hyperglycemia, increased vascular resistance, redistribution of body fat to the viscera, and accelerated biological aging ( 40 ). These changes can directly lead to insulin resistance and hypertension and thus represent a mechanism by which loneliness may drive the development of metabolic syndrome.…”
Section: Loneliness Leads To Pathophysiological Changes: a Chronic St...mentioning
confidence: 99%